Psychosocial and physical long-term outcome in patients with a history of takotsubo cardiomyopathy or myocardial infarction - a multi-centered case control study. Issue 8 (13th September 2020) - Olliges, E.; Burgdorf, C.; Ladwig, K.H.; Moeller, C.; Deftu-Kloes, D.; Pohl, S.; Ruettner, B.; Richardt, G.; Meissner, K.; Steger, A.; Goetzmann, L.; Ronel, J.
ABSTRACT: Physical long-term impacts of Takotsubo Cardiomyopathy (TTC) remain controversial and an underestimation of their severity becomes increasingly evident. Even less is known about mental long-term impacts of TTC. This study aims at a better understanding of the physical and mental long-term effects of TTC in comparison to myocardial infarctions (MI). On average 5 years after disease onset, 68 TTC patients and 68 age- and sex-matched MI patients were assessed for disease-related quality of life, depression, anxiety, chronic stress, social support, resilience, and life events prior to disease onset. Scores of TTC and MI patients were compared to each other and to normative references values. Regression analyses were used to evaluate the predictive value of the number of life events prior to disease onset for physical and mental long-term outcomes. Both groups displayed higher scores in depression and anxiety, higher levels of chronic stress, and lower scores in physical and mental quality of life in comparison to norm samples, while social support did not differ from norms. No differences between the two patient groups were observed. Within both groups, the majority of patients (TTC: 69.1%; MI: 60.3%) reported stressful life events prior to disease onset. In TTCs and MIs, the number of events had a significant impact on long-term mental health and chronic stress. Notably, both patient collectives scored higher in resilience than healthy controls. Results suggest negative long-term impacts of TTC on mental and physical wellbeing, comparable to those of MI. Besides a good somatic-medical care, psychotherapeutic support, including the development of functional coping strategies, might be warranted for TTC patients. The long-term impact of TTC should be taken as serious as that of MI.